The Institutionalization of Knowledge in an Organization - Wiseman, Erica (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
In order to strategically manage knowledge in an organization it is critical to understand how knowledge is embedded at the organizational level. However the processes through which new knowledge is actually institutionalized are mainly unspecified. The design of an exploratory study of the process of institutionalizing knowledge will be discussed. Afin de gérer stratégiquement les connaissances d’une organisation, il est fondamental de comprendre comment les connaissances sont intégrées dans les différents niveaux de l’organisation. Cependant, les procédures avec lesquelles les nouvelles connaissances sont réellement institutionnalisées ne sont généralement pas spécifiées. La conception d’une étude exploratoire du processus d’institutionnalisation des connaissances est présentée.